PEMANFAATAN LAHAN PENYANGGA DAN KEBIJAKAN PEMERINTAH UNTUK MENGURANGI KONFLIK MANUSIA DENGAN ORANGUTAN (PONGO ABELII LESSON): STUDI KASUS PELEPASLIARAN ORANGUTAN DI TAMAN NASIONAL BUKIT TIGAPULUH, RIAU - Wanda Kuswanda (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
The demage of forest areas and land clearing in buffer zones for plantation, agricultural and village areas has resulted in widespread human-wildlife conflicts, such as orangutans. Orangutans out of the forests to feed and destroy plant, including the case in Bukit Tigapuluh National Park (BTNP). This study aimed to obtain information on community characteristics, land use patterns in buffer zones as well as government policies for conflict mitigation between human and orangutans reintroduction at BTNP, Riau Province. The research was conducted in the buffer zone and the park area, from August to November 2016. Data were collected with questionnaires distribution, structured interviews and Focus Discussion Group on related communities and institutions. Data analysis are using frequency tables and descriptive analysis. Communities in the buffer zone of BTNP, especially in Siambul and Talang Langkat villages, are working as farmers and educated only to junior high school so that dependence on natural resources is very high and be triggers conflict with orangutans. The utilization of dominant land for oil palm and rubber plantations. Other cultivated plants are chocolate, banana, grapefruit, durian as well as jengkol. This plant species of cultivation are very interesting for orangutans so that out of the forest to consuming. Orangutan conflicts are occurred in the Batang Cinaku and Batang Gangsal Districts. Recommendations to conflict mitigation is the habitat improvement in national park with feed, the development of alternative economic for communities such as honeybees and farms, the establishment of a orangutan monitoring team, socialization and counseling about habits, behavior and benefit orangutans, enforcement of encroachment and illegal logger, the revitalization of the system and the culture of agriculture move, especially on Talang Mamak and the Melayu Ethnics. This recommendation is also expected to be a reference for the government in North Sumatra because the orangutans conflict is found also at Langkat, South Tapanuli and West Pakpak. Keywords: community, orangutan conflicts, land, oil and national parks